MAZ-mediated N6-methyladenosine modification of ZEB1 promotes hepatocellular carcinoma progression by regulating METTL3 - Di Li; Li Xu; Ruyuan Liu; Zhaonv Yao; Chuanjun Zheng; Song Jin; Xuefeng Guo; Zhengbao Zhang; Shengkui Tan; Xiaonian Zhu (Journal of Translational Medicine)
Abstract Background Hepatocellular carcinoma (HCC) has a hidden onset and high malignancy. Its high metastasis, high recurrence, and short survival time have always been a difficult and hot spot in clinical practice. Our previous study revealed that myc-associated zinc finger protein (MAZ) is highly upregulated in HCC tissues and may promote the proliferation and metastasis of HCC cells by inducing the epithelial-mesenchymal transformation (EMT) process. However, the specific regulatory mechanism by which MAZ functions as an oncogene in HCC has still not been fully elucidated. Methods Immunohistochemical staining and bioinformatics analyses were conducted to measure the expression of MAZ, key m6A enzymes, and ZEB1 in HCC tissues. RNA sequencing (RNA-seq) of MAZ knockdown HCC cells and human mRNA m6A sequencing (m6A-seq) of HCC tissues were intersected to screen the downstream targets for both MAZ and m6A methylation. The correlations between MAZ and its targets were analyzed by dual-luciferase assays and cell rescue experiments. Results Here, we report for the first time that MAZ is involved in m6A methylation of HCC by targeting the transcriptional regulation of key m6A enzymes. MAZ expression was significantly correlated with the expression of key m6A enzymes in HCC tissues and cell lines. Moreover, MAZ could bind to the promoters of key m6A enzymes, and multivariate Cox regression analysis suggested that MAZ and METTL3 expression were independent risk factors for the survival of HCC patients. Through RNA-seq and m6A-seq, we screened out EMT regulators ZEB1 and TRIM50 as the downstream targets for both MAZ and m6A methylation. Mechanistically, m6A sites with high confidence in ZEB1 and TRIM50 mRNA were identified by SRAMP, and there were significant relationships between ZEB1 and METTL3 in HCC tissues and cells. A nomogram model was established to better display the combined effect of MAZ, METTL3, and ZEB1 on HCC prognosis. Conclusions Our study revealed a promising clinical application of MAZ, METTL3, and ZEB1 in HCC prognosis, further suggesting that MAZ can be used as a potential molecular biomarker for HCC diagnosis and prognosis.